1988
DOI: 10.1182/blood.v71.2.448.448
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the plasticizer di-2-ethylhexyl phthalate on the survival of stored RBCs

Abstract: Recent in vitro studies have shown that di-2-ethylhexyl-phthalate (DEHP) inhibits the deterioration of RBCs during refrigerated storage in containers that use this compound as a plasticizer. The experiments described in this report were designed to assess whether this in vitro protective effect of DEHP would result in a prolonged in vivo survival of RBCs infused into normal human recipients. Whole blood collected from ten normal donors was stored for 35 days in citrate-phosphate- dextrose-adenine (CPDA-1) anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 20 publications
0
54
0
Order By: Relevance
“…14 Moreover, the absence of plasticizer, present in human blood bags and reported to extend human RBC survival, may also be responsible. 15 It is important to note that the FDA requirement for 75% posttransfusion survival at 24 hours represents an average. Indeed, some units of RBCs stored under approved conditions for the appropriate length of time have substantially worse survival.…”
Section: Discussionmentioning
confidence: 99%
“…14 Moreover, the absence of plasticizer, present in human blood bags and reported to extend human RBC survival, may also be responsible. 15 It is important to note that the FDA requirement for 75% posttransfusion survival at 24 hours represents an average. Indeed, some units of RBCs stored under approved conditions for the appropriate length of time have substantially worse survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of PVC blood bags containing DEHP has been permitted in Japan without any regulation other than storage at low temperatures because DEHP has been found to be effective in preserving stored red blood cells (RBCs). 15 We recently developed a prototype of a novel and biologically safer blood container consisting of UV-irradiated PVC sheets 16 from which the elution of DEHP was almost suppressed. On evaluating the safety of the prototype, we found that the hemolytic ratio of the heparinized bovine blood stocked in the container was lower than that of the blood stored in normal PVC blood bags (data not shown).…”
Section: Introductionmentioning
confidence: 99%
“…Despite research on alternative plasticizers including TOTM 14 or BTHC 15 or other polymers like polyolefines, 15,16 DEHP is still the plasticizer of choice for RBC storage containers because of the positive effect of DEHP on RBC stability. The presence of DEHP resulted in better retention of normal morphology, 17 enhanced osmotic stability, 18,19 decreased hemolysis, 18,20 and improved in vivo recoveries 24 hours after transfusion. 14,20 The plasticizer di(isononyl) cyclohexane-1,2dicarboxylate (DINCH), also known as Hexamoll DINCH (BASF SE, Ludwigshafen, Germany) is currently being discussed for its potential use in blood bags.…”
mentioning
confidence: 98%